Advances in the concept of functional foods and feeds: applications of cinnamon and turmeric as functional enrichment ingredients - Kumar, Harsh; Dhalaria, Rajni; Guleria, Shivani; Sharma, Ruchi; Cimler, Richard; Dhanjal, Daljeet Singh; Chopra, Chirag; Kumar, Vijay; Manickam, Sivakumar; Siddiqui, Shahida Anusha; Kaur, Talwinder; Verma, Narinder; et al. (Critical reviews in food science and nutrition, 2025)
Spices are a rich source of vitamins, polyphenols, proteins, dietary fiber, and minerals such as calcium, magnesium, iron, and zinc, all of which play an important role in biological functions. Since ancient times, spices have been used in our kitchen as a food coloring agent. Spices like cinnamon and turmeric allegedly contain various functional ingredients, such as phenolic and volatile compounds. Therefore, this review aims to summarize the current knowledge about the nutritional profiles of cinnamon and turmeric, as well as to analyze the clinical studies on their extracts and essential oils in animals and humans. Furthermore, their enrichment applications for food products and animal feed have also been investigated in terms of safety and toxicity. Numerous studies have shown that cinnamon and turmeric have various health benefits, including the reduction of insulin resistance and insulin signaling pathways in diabetic patients, the reduction of inflammatory biomarkers, and the maintenance of gut microflora in both animals and humans. The food and animal feed industries have taken notice of these health benefits and have begun to promote cinnamon and turmeric as healthy foods. This has resulted in the development of new food products and animal feeds that contain cinnamon and turmeric as primary ingredients, which have been deemed an effective means of promoting cinnamon and turmeric's health benefits.
Keywords: Plant Extracts; functional feed; nutriční hodnota; Humans; oleje prchavé; Animal Feed; Cinnamon; Spices; lidé; zvířata; Functional Food; rostlinné extrakty; Curcuma; functional food; skořicovník ceylonský; Nutritive Value; krmivo pro zvířata; Food, Fortified; fortifikované potraviny; enrichment; koření; turmeric; Cinnamomum zeylanicum; Oils, Volatile; Animals; funkční potraviny